The efficiency loss of capital income taxation under imperfect loss offset provisions - Syed M. Ahsan; Panagiotis Tsigaris (Center for Economic Studies and ifo Institute (CESifo), 2008)
The importance of capital loss offset provisions in a world of risk is well documented in the tax literature. However, the potential deadweight losses owing to imperfect offset has not been fully explored. This paper develops a framework whereby that investigation can be carried out and utilizes numerical simulations to investigate the size of potential losses. Results show that when the government and private sector are equally efficient in handling market risk, welfare losses owing to the absence of offset provisions could be substantial. Under plausible assumptions about attitudes towards risk and time preference, and with a capital income tax rate of forty percent, over sixty cents per dollar of tax revenue raised would be dissipated. In contrast, full loss offset would reduce that loss to approximately fourteen cents.
Keywords: H00; H21; H22; 330; capital income taxation; uncertainty; deadweight loss; loss offset provisions; Kapitalertragsteuer; Entscheidung bei Unsicherheit; Wohlfahrtseffekt; Steuerbegünstigung; Steuertheorie